Is It Matters to Have a Higher Education for the Young People Behavior on the Internet? - G. F. Gabdrakhmanova (Высшее образование в России)
The article solves the problem of comparing the influence of two factors – the presence of higher education and generational affiliation – on digital competence and on the behavior of young people in the Internet space. Approaches arising from the theory of digital inequality are involved to solve it. They are problematizing the importance of socio-demographic and other population’s characteristics for the use of information and technological innovations. Another important study aspect was the theory of generations. It made it possible to identify generations Y and Z, formed under the conditions of technological changes at the turn of the 20th-21st centuries. The article focuses on representatives of Generation Z. Their digital competence and behavior on the Internet is compared with higher education. Sources of the study: a sociological survey of young people in 8 federal districts of Russia conducted in 2023, data from analytical companies subjected to secondary assessment, materials from official statistics.Education is the third most important factor influencing the digital inequality of Russian youth, two other reasons are behind – place of residence and material security. Higher education maintains its position in ensuring the digital competence of young people. However, its presence does not affect the behavior of young people on the Internet. Representatives of Generation Z, who today are still studying at or enrolling in Russian universities, are not inferior to those who have higher education in terms of the information and technological innovations level of use. Digital natives are noticeably more likely than millennials to evaluate the Internet as a source of education, self-education, and broadening their horizons. Such a request creates new tasks for higher education. The article concludes with recommendations for Russian universities regarding their work in social media that is significant for generation Z.